Structural behaviour of CFRP strengthened beam-column connections under monotonic and cyclic loading. (October 2021) - Tafsirojjaman, T.; Fawzia, Sabrina; Thambiratnam, David P.
Abstract: Welded beam-column connections may be vulnerable to failure under cyclic loading conditions. These connections might require strengthening to resist static and cyclic loads as they may exhibit inadequate capacity due to the design errors or material properties degradation because of severe environmental effects or an increase in service loads. With this in mind, a series of full-scale experiments have been conducted to investigate the behaviour of the bare and strengthened welded beam-column connections under both monotonic and large-displacement cyclic loading. Carbon fibre reinforced polymer (CFRP) is used as the strengthening material in the present study along with epoxy adhesive as the bonding material. The experimental study conclusively showed the benefits of CFRP composites to improve the performance of welded connections under both monotonic and cyclic loadings. Under monotonic loading, the ultimate moment capacity, stiffness, dissipation of energy and ductility of the welded connections improved by strengthening with CFRP. Additionally, under cyclic loading, the CFRP strengthened welded connections showed improvement in moment hysteresis behaviour, higher stiffness and energy dissipation capacity compared to their bare counterparts. Moreover, the experimentally obtained moment capacities match reasonably well with the theoretically predicted moment capacities.